Small field dosimetric verification and patient specific quality assurance for cyberknife radiosurgery system using 3d gel dosimeters - Kafi, Md Abdullah Al (2024)
CyberKnife (CK) stereotactic radiotherapy/radiosurgery system uses very small intensity-modulated radiation therapy fields or field segments to treat tumors with high dose gradients. To overcome the limitations for dosimetry of those small fields, small volume, high resolution and tissue-equivalent detectors are recommended. The joint IAEA and AAPM international code of practice (CoP), TRS 483 provides field output factor (FOF) measurement guidelines and field output correction factors for a series of small field detectors. The CoP strongly recommends additional measurements and data collection with available detectors and more new ones for CK. The present study focused on using 3D polymer gel, EBT3 film, Monte Carlo simulation and some other commercially available detectors for the measurement and verification of FOFs for the small field cones (0.50 cm to 60.0 cm) available in CK system. When compared with the Monte Carlo data, the maximum percentage difference for the FOF for Edge detector and PTW diode was found to be 0.99% and 0.96% respectively for 0.75 cm cone, whereas it is 3.33% for diamond detector for 0.50 cm cone. For Pinpoint ionization chamber, the maximum difference is 1.72% for 0.75 cm cone when measured in water and for Semiflex chamber; it is 2.4% for 1.25 cm cone. The maximum difference for all plastic scintillation detectors were 1.89%. For EBT3 film, the difference is 1.86%, whereas it is 3.93% for 3D polymer gel for the smallest 0.50 cm cone. The results of this study have proved the suitability of an in-house built 3D polymer gel dosimeter, several commercially available detectors, and GafChromic films for the CK system. For the verification and quality assurance (QA) of hypofractionated stereotactic radiotherapy or radiosurgery treatments deliveries, the conventional two dimensional and low resolution techniques are not adequate due to high dose gradient surrounding the tumor. Hence, high resolution tool with 3D capability needs to be introduced those treatment verifications. This study employed a recently developed 3D radiochromic polymer gel patient-specific quality assurance (PSQA) system named CrystalBall to verify CK treatment plans. Fifteen CK patients with different diagnoses were selected randomly and the delivered dose distributions were compared with that of planned by means of 3D gamma passing rates at user-selected acceptance criteria using VOLQA software. The 3D gel gamma passing rates were validated by comparing with GafChromic EBT3 film 2D gamma passing rates using PTW Verisoft software. For 3D CrystalBall gel, the average gamma index assing rates for 2% dose difference ( D) and 2 mm distance to agreement (DTA) were (81.7 ± 10.3) %, (91.1± 6.4) % and (95.6 ± 3.9) % for 10%, 20% and 30% cut-off doses respectively. For 3% D and 3 mm DTA, the average gamma were (89.8 ± 6.3) %, (96.3 ± 3.0) % and (98.8 ± 1.1) % for 10%, 20% and 30% cut-off doses respectively. The results of this study have proved the suitability of the new 3D CrystalBall system for PSQA as a part of quality assurance for CK system.